Psychological interventions for acute psychiatric inpatients with schizophrenia-spectrum disorders: A systematic review and meta-analysis. (December 2020) - Barnicot, K.; Michael, C.; Trione, E.; Lang, S.; Saunders, T.; Sharp, M.; Crawford, M.J.
Abstract: Background: Acute inpatient psychiatric wards are important yet challenging environments in which to implement psychological interventions for people with schizophrenia-spectrum disorders. No meta-analysis to date has evaluated whether psychological interventions are effective in this context. Methods: We systematically searched Embase, Medline and PsycInfo databases for randomised controlled trials (RCTs) of psychological interventions implemented in acute inpatient psychiatric settings with individuals with schizophrenia-spectrum disorders. We conducted random effects meta-analyses of between-groups outcomes at post-intervention and relapse/re-hospitalisation rates by follow-up. Results: Twenty-nine trials were suitable for meta-analysis. Psychological interventions improved post-intervention positive symptoms, social functioning and treatment compliance and reduced the risk of relapse/ re-hospitalisation, relative to control conditions. Analyses of specific intervention effects found positive effects of psychoeducation on several key outcomes (power > 80%) and preliminary evidence for positive effects of acceptance and commitment therapy (ACT), cognitive behaviour therapy (CBT) and metacognitive training (MCT) on some outcomes (power < 80%). Conclusion: Psychological interventions can be helpful for acute inpatients with schizophrenia-spectrum disorders. However, risk of bias was often high or unclear, and some analyses were underpowered. Further research should use more rigorous RCT designs and publish meta-analysable data on positive symptoms, general psychopathology, relapse/ re-hospitalisation, social functioning and treatment compliance. Highlights: We reviewed trials of psychological interventions for acute inpatient schizophrenia. Psychological interventions improve positive symptoms, functioning and compliance. Psychological interventions reduce risk of relapse or re-hospitalisation. Psychoeducation improves psychopathology and functioning and reduces relapse. Specific evidence for other psychological interventions is preliminary or absent.